Seismic response mitigation of girder displacement of cable-stayed bridge using inerter systems. (May 2022) - Zhang, Hongli; Ye, Zhiming; Chen, Xu; Yao, Wenjuan
Abstract: Cable-stayed bridges have been widely utilized as transportation hubs in mountainous and coastal areas. Once these bridges are damaged during earthquakes, the routine for rescue operations will be interrupted, leading to enormous life and financial loss. Since damage of cable-stayed bridges are mainly caused by excessive displacement of main girders, this paper considers mitigating the displacement demands by implementing inerter systems between tower and main girder. Following brief introduction of inerter systems, a simplified three degree-of-freedom (DOF) dynamic model of a cable-stayed bridge prototype is established and verified by refined finite element (FE) model. Then the design parameters of inerter systems are optimized based on the dynamic amplification factor ( DMF ) method, while the influence of each parameter on the performance is discussed in detail. To further investigate the efficiency of these systems, the seismic responses of cable-stayed bridge with different inerter devices are computed and compared with the prototype, as well as system with conventional viscous dampers (VD). From the analytical results, the inerter systems are demonstrated effective in alleviating displacement demands of main girder of cable-stayed bridges and outperforming the commonly used VD. This study is believed able to provide basis for engineering application of inerter systems on cable-stayed bridges to improve the seismic performance and reliability against earthquakes.